Analysis of voltage sag compensation in distribution systems using a multilevel DSTATCOM in ATP/EMTP (2015)
Voltage sags are the most common power quality disturbances in electrical facilities. It may cause malfunction in sensitive equipment and process interruption. The distribution static compensator (DSTATCOM) is a device that can compensate voltage sags by injecting reactive power into distribution system. This paper shows the influence on voltage sags characteristics by the presence of twelve-pulse DSTATCOM in the modified IEEE-13 distribution system. The analysis is performed by means of a random generation of disturbances using a MATLAB routine to identify the critical buses of the test system. Further, the DSTATCOM model taking advantage of the available elements from ATP/EMTP software is described. Simulations show that when DSTATCOM is placed directly to affected bus it is possible to obtain a complete mitigation of the voltage sag. Finally, the relation between the reactive power injected by DSTATCOM, the type of voltage sag and the location of affected bus is considered.